Determinants of Iranian agricultural consultants’ intentions toward precision agriculture: Integrating innovativeness to the technology acceptance model - Somayeh Tohidyan Far; Kurosh Rezaei-Moghaddam (Journal of the Saudi Society of Agricultural Sciences)
Environmental crises and global concerns toward the consequences and side impacts of conventional agricultural systems and agricultural activities on environment resulted in the viewpoint of the necessity of changing mental patterns regarding sustainable farming systems. Different agricultural methods such as precision agriculture have been presented to respond to environmental problems in recent years. The purpose of this research was to investigate factors influencing agricultural personnel and consultants’ attitude and behavioral intention to use precision agricultural technologies. The survey research and multistage random sampling were used to collect data from 183 agricultural consultants in Agricultural Engineering and Technical Consulting Services Companies. The results of structural equation modeling indicated that agricultural personnel and consultants in Fars Province intended to use precision agricultural technologies. Based on the results the behavioral attitude is the most important determinant of experts’ intention toward the use of the precision agriculture technologies. Also individual innovativeness, attitude of confidence, perceived ease of use and perceived usefulness of precision agricultural technologies affected on the behavioral attitude and behavioral intention to use. According to the results, practical suggestions have presented to use these technologies in Iran.